Corrina, Corrina [videorecording (DVD)] - Goldberg, Whoopi, 1955-; Liotta, Ray; Majorino, Tina, 1985-; Nelson, Jessie (New Line Home Video, 1999)
A funny, heart-warming story of a newly widowed man struggling to raise his little girl, and the woman who brings magic and laughter back into their lives when she comes to be their housekeeper.